Esophageal Bronchial Artery Fistulaization: A Complication of an Endobronchial Ultrasound. Issue 4 (10th April 2020) - Jadeja, Sonal; Green, Kevin; Shuja, Asim; Malespin, Miguel; De Melo, Silvio
ABSTRACT: Bronchial artery pseudoaneurysms are an extremely rare cause of upper gastrointestinal bleeding. The presence of a bronchial artery pseudoaneurysm resulting in an esophageal fistula is an entity that, to our knowledge, has yet to be described. Successful management requires an interdisciplinary approach to guide closure of the defects. We present a novel case of an esophageal fistula and bronchial artery pseudoaneurysm resulting from an endobronchial ultrasound-guided transbronchial needle aspiration successfully managed by endoscopic therapy and coil embolization.